Chemical cross‐linking of xenopericardial biomeshes: A bottom‐up study of structural and functional correlations. (22nd January 2019) - Grebenik, Ekaterina A.; Istranov, Leonid P.; Istranova, Elena V.; Churbanov, Semyon N.; Shavkuta, Boris S.; Dmitriev, Ruslan I.; Veryasova, Nadezhda N.; Kotova, Svetlana L.; Kurkov, Alexander V.; Shekhter, Anatoly B.; Timashev, Peter S.
Abstract: Decellularized bovine pericardium (DBP)‐based biomeshes are the gold standard in reconstructive surgery. In order to prolong their stability after the transplantation, various chemical cross‐linking strategies are employed. However, structural and functional properties of the biomeshes differ in dependence on the cross‐linker used. Here, we performed a bottom‐up study of structural and functional alterations of DBP‐based biomeshes following cross‐linking with hexamethylene diisocyanate (HMDC), ethylene glycol diglycidyl ether (EGDE), 1‐ethyl‐3‐(3‐dimethylaminopropyl)carbodiimide (EDC) and genipin. The in vitro cytotoxicity tests supported their clinical applicability. Their structural differences (eg roughness, fibre thickness, pore morphology) were evaluated using the two‐photon confocal laser scanning, atomic force, scanning electron and polarized light microscopies. HMDC and EDC samples appeared to be the roughest. Complex mechanical trials indicated the tendency to reduced Young's Modulus and mechanical anisotropy values of DBP upon cross‐linking. The lowest mechanical anisotropy was found in EDC and genipin sample groups. In vitro collagenase susceptibility was the highest for EDC samples and the lowest for EGDE samples. The comparative analysis of the results allowed us to recognize the strengths and weaknesses of each cross‐linker in relation to a particular clinical application. Abstract : Cross‐linking‐assisted personalization of xenopericardial biomeshes for specific clinical purposes.